Android-Based Student Behavior Study using Cloud Computing Infrastructure - Ardi Hutagalung, Gabriel; Nugroho, Okvi (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2020)
Android-based student behavior data collection system is a system to improve student data collection so that student data can be seen as fellow students, besides this system makes it easy for students to see grades and absences for 1 semester so that accessing grades and absences is very useful for students' parents, design Andorid-based student behavioral data collection system uses the UML (Unified Modeling Laanguage) design method, the purpose of this system is to improve student data collection, absences, grades and achievements with a computerized system that users can access student data online. The result of system design is a system that can be used by students, lecturers, to make it easier to collect student data. Keyword : Unified Modelling Language, Online, Student, Andorid.